A review of some recent studies on the stable isotope profiling of methylamphetamine: Is it a useful adjunct to conventional chemical profiling?. Issue 1 (January 2015) - Collins, Michael; Salouros, Helen
Abstract: This paper reviews a body of work published by the authors over a number of years aimed at providing a complementary "signature" to conventional chemical profiling of methylamphetamine. The work, beginning in 2009, was undertaken because of the changing nature of clandestine methylamphetamine manufacture which has seen a dramatic rise in production and a major shift to a higher quality product. As manufacturing methods changed and methylamphetamine purity increased some conventional drug profiling techniques became less useful as an intelligence tool. For instance, the value of the organic impurity profile, a mainstay of conventional profiling, decreases as there are fewer impurities present in seized samples. However, whilst many seizures may contain less conventional chemical intelligence another property of the methylamphetamine molecule is always available, i.e. the light element stable isotope ratios. The stable isotope ratios of carbon, hydrogen and nitrogen are an integral part of the methylamphetamine molecule itself. This review describes previous work by the authors and by researchers in other national laboratories to investigate and implement the use of stable isotope ratios as an everyday methylamphetamine profiling tool. It also looks at how powerful this technique can be when used to compare samples from different seizures.